MDMA-Induced BV2 Microglial Cell Activation in Vitro - Nasir Mohamad; Nor Suliana Mustafa; Nor Hidayah Abu Bakar; Ramli Musa; Liyana Hazwani Mohd Adnan; Nor Zidah Ahmad; Mohd Nazri Mohd Daud; Zulfa Izza Mohamed Hashim (Shahid Beheshti University of Medical Sciences, 2022)
Introduction: 3,4-Methylenedioxymethamphetamine (MDMA) is a type of psychostimulant drug that induces neurotoxicity. Even though several psychostimulant substances activate microglia, little is known about MDMA's effects on these cells, and evidence of MDMA-induced microglial activation is equivocal. Material and Methods: This study employed a murine microglial cell line, BV2, to examine the effects of MDMA on the microglia morphological changes and the survival of microglia in vitro. MDMA was incorporated into the media at the time of plating and cell number and levels of mitochondrial dehydrogenase activity (MTT) were determined in vitro. The level of pro-inflammatory cytokine TNF-α was also determined. Result: Treatment of BV2 cells with MDMA resulted in morphological changes, reduced cell viability after 24h incubation with the inhibitory concentration (IC50) value of 243.6 µg/mL, and increase TNF-α level in a dose-dependent manner. Conclusion: These findings proposed that MDMA could induce BV2 microglial cell activation in vitro and suggested that it has an important role in the development of MDMA use disorder.